Territorialités aymaras et gouvernementalités transnationales néolibérales – Sécurité et « développement avec identité » en zone frontalière chilienne - Laetitia Rouviere (Nuevo mundo - Mundos Nuevos, 2015)
The emergence of cross-border and autochthonous territories affects the administration of national borders. Based on the Aymara case in Chile, this paper outlines that the government of national territory also finds continuity, if not a complement, in the legitimization of a local and cross-border political initiative. On the triple border between Chile, Peru and Bolivia, the mayors of fifty-seven localities gathered in an association called the “Strategic Alliance Aymaras without Borders” promote the elaboration of joint “development with identity” policies. The observation of the stage prior to this elaboration allows lighting up an effect of securitization of these borderlands, through the active involvement of local authorities in the control of cross-border flows and through the homologation of border policies in the three countries. The Chilean local authorities lead the project and take over most International Financial Institutions’ requisites. This contributes in the diffusion of norms of actions on political and territorial peripheries of Chile and beyond: in Peruvian and Bolivian border localities as well as at the national level of border administration of those states. The development of indigenous population in this cross-border context would thus entail, starting from the bottom a collaboration between rival states among which Chile confirms a leader position.